Home furnishings - Davis, Mary E. (My University, 1904)
Introduction: In treating of furnishings we must begin by defining the word as it is to be used and so considered in this production. In its natural and general meaning, furniture (French “mobilier”) represents everything that is movable, transportable and easy to place in security. We intend to consider the house neither constructively nor architecturally, but as a dwelling-place, in that it relates to all internal adornment and arrangement. As, however, the decoration and fitting up of the rooms are often essentially dependent upon the construction of the house and upon its divisions, and were more especially so in the antique dwelling, these latter points must not remain altogether unconsidered. Furnishings or adornment of a house or dwelling are regarded in too many cases as of secondary importance, even by those who are intellectually strong and appreciate modern culture and training. It also happens that for want of individual knowledge even those who mean well, commit the arrangement and adornment of their home to tradesmen, with the feeling that he will best understand what ought to be done, but he does not and can not but follow the dictates of fashion. We regret this state of things when we consider the important part that home plays in our lives and how much its beauty can add to our pleasures of existence and how much the mere helping to produce such beauty is in itself a source of positive delight for even when we are called upon to exercise judgment in selecting materials or arranging furniture we are doing artist's work, a responsible womanly work which brings with it real enjoyment. Much can be learned by studying the art of furnishing, and much more can be learned by studying the history of the art of furnishing and its relation to civilization…
Citation: Davis, Mary E. Home furnishings. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Furniture; Home Improvement; Decorations; History of Home Furnishing; Theses